The Effect of the Addition of Copper Particles in High-Density Recycled Polyethylene Matrices by Extrusion - Azocar-Guzman, M; Azocar-Guzman, M; Walter, M; Walter, M (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
In this study, the effect of the recycling process and copper particle incorporation on virgin and recycled pellet HDPE were investigated by thermo-chemical analysis, mechanical characterization, and antibacterial analysis. Copper particles were added to pellet HDPE, virgin and recycled, using a tabletop single screw extruder. Some copper particles, called copper nano-particles (Cu-NPs), had a spherical morphology and an average particle size near 20 nm. The others had a cubic morphology and an average particle size close to 300 nm, labeled copper nano-cubes (Cu-NCs). The thermo-chemical analysis revealed that the degree of crystallization was not influenced by the recycling process: 55.38 % for virgin HDPE and 56.01% for recycled HDPE. The degree of crystallization decreased with the addition of the copper particles. Possibly due to a modification in the structure, packaging organization, and crystalline ordering, the recycled HDPE reached a degree of crystallization close to 44.78% with 0.5 wt.% copper nano-particles and close to 36.57% for the recycled HDPE modified with 0.7 wt.% Cu-NCs. Tensile tests revealed a slight reduction in the tensile strength related to the recycling process, being close to 26 MPa for the virgin HDPE and 15.99 MPa for the recycled HDPE, which was improved by adding copper particles, which were near 25.39 MPa for 0.7 wt.% copper nano-cubes. Antibacterial analysis showed a reduction in the viability of E. coli in virgin HDPE samples, which was close to 8% for HDPE containing copper nano-particles and lower than 2% for HDPE having copper nano-cubes. In contrast, the recycled HDPE revealed viability close to 95% for HDPE with copper nano-particles and nearly 50% for HDPE with copper nano-cubes. The viability of S. aureus for HDPE was lower than containing copper nano-particles and copper nano-cubes, which increased dramatically close to 80% for recycled HDPE with copper nano-particles 80% and 75% with copper nano-cubes. © 2022 by the authors.